Analisis Gaya Kepemimpinan Situasional di Satu Sekolah Dasar Kecamatan Pagar Merbau - Dian Kartika Sari; Syifaushudur Harefa; Wildansyah Lubis; Winara Winara (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to describe the dynamics of school leadership at a primary school affected by limited leadership experience and health-related constraints. Using a descriptive qualitative approach and in-depth interviews with several teachers, the findings reveal that the principal adopts a situational leadership style characterized by flexible and delegative practices. The principal places significant trust in senior teachers to carry out daily operational functions and decision-making processes. While this strategy fosters teacher autonomy and ensures the continuity of school activities, it also reveals weaknesses in supervision, quality control, and the symbolic presence of leadership. The lack of direct supervision results in unclear performance evaluations and weak program coordination. The study concludes that the effectiveness of situational leadership relies heavily on the strength of interpersonal relationships among staff and the existence of supportive internal systems. It is recommended that the principal strengthen the management team and establish a more structured communication system to sustain leadership quality and educational standards.